The drum and its significance for the interpretation of the Old Testament from an African perspective: Part one - Rudolph De Wet Oosthuizen (Verbum et Ecclesia, 2016)
Recent developments in South Africa opened the doors of opportunity for Old Testament scholars to position themselves in terms of Africa and to allow the African context to play a more explicit role in the interpretation of the Bible. An awareness of the significance of the (South) African context for the interpretation of the Old Testament in South Africa can inform the construction and refinement of the comparative paradigm as a reading strategy. In consequence, it might not only serve the communication of the message, but also facilitate a dialogue between the text and the contemporary reader and imbue the comparative method as a reading strategy. Being aware of the significance of music and its function regarding expression of African religion and spirituality, the article explores aspects of music and its potential to inform a particular reading, with specific reference to the drum. (Whilst the focus in Part 1 is more on some hermeneutical aspects as pertaining to a specific reading strategy, Part 2 is to explore the significance of music for the interpretation of the Old Testament with specific reference to Psalm 150). Intradisciplinary and/or interdisciplinary implications: The contribution attempts to illustrate that, in our encounters with the biblical text, we need to move beyond a historical descriptiveanalysis of the text or defining its significance in linguistic terms only. In so doing, the comparative paradigm is augmented by allowing insights from various disciplines to inform the reader. Keywords: Music; 'Hemeneutics'; 'African Reading' of the Old Testament